On the Endurance and Limits of Disagreement: Romans 14–15 and Contemporary Moral Conflicts - Errington, Andrew (Studies in Christian ethics, 2025)
The apostle Paul's arguments in Romans 14–15 have played an important role in the history of Christian thinking about moral disagreement. In recent years, this passage has been significant in debates about sexuality. Yet Paul's arguments are more complex than is sometimes recognised. They support a distinction between moral disagreements that should be endured within a Christian community and disagreements that should not be endured. More than ‘agreeing to disagree’, the fruitful endurance of disagreement involves openness to ongoing dialogue, in hope of final consensus. These arguments have the potential to enrich our thinking about contemporary moral disagreements, including those appearing on the horizon in relation to questions associated with assisted dying. Reflection on these questions also points to a role that might be played by academic Christian ethics in enduring disagreements.